Factors Affecting the Effectiveness of Rural and Urban Land and Building Tax Revenue (PBB-P2) in Central Maluku District - HUKOM, Lina Meilani; RUMERUNG, Dientje; NIKIJULUW, Jeanee Belthia (Journal of Tourism Economics and Policy, 2024)
The purpose of this research is to determine the influence of taxpayer compliance, taxation systems and procedures, and the behavior of tax officials on the effectiveness of PBB-P2 revenue in Central Maluku Regency. The type of research used is quantitative research. This research was conducted with a population of all tax collecting of the land and building in rural and urban (PBB-P2) taxpayers of 88,285. Sampling was taken by distributing questionnaires based on the Slovin formula to 100 taxpayer respondents. Hypothesis testing was carried out using multiple linear analysis using the Statistical Product and Service Solution (SPSS) version 29 test tool. The research results show that taxpayer compliance, tax systems and procedures, behavior of tax officials have a positive and significant and simultaneous effect on the effectiveness of revenue. . As an implication, by paying attention to the effectiveness of the performance of the tax apparatus and increasing the capacity of human resources owned by the Regional Revenue Agency, it determines the services provided optimally to taxpayers with tax systems and procedures that are easy for taxpayers to understand, making it easier for taxpayers to make tax payments tax collecting of the land and building in rural and urban (PBB-P2) and can influence the effectiveness of tax collecting of the land and building in rural and urban (PBB-P2) acceptance.